Management of Nigerian Universities in the 21st Century for Effective Goal Attainment - Okai, Okai Ndubuisi; Okai, Faith Izeuma (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The management of university system in the 21st century demands adaptive, innovative, and strategies approaches to ensure the attainment of institutional goals in an increasingly dynamic global environment. The paper examines management of university in Nigeria in 21st century for goal attainment. It highlights the impact of globalization, technological advancement, and evolving labour market demands on university governance, curriculum design, faculty development, and students’ engagement. The paper emphasized the need for participatory leadership, data-driven decision-making, quality assurance mechanisms, and sustainable, funding models as core elements of effective university management in the 21st century that teaching and learning in Nigeria universities should be managed to reflect 21st century education, and university administrator should foster strong university industry linkages for improving the programme of the university, it explores the role of digital transformation in enhancing teaching, research, and institutional operations, while addressing challenges such as inadequate infrastructure, policy inconsistencies, and brain drain, particularly within the Nigerian context. The paper advocates for the adoption of evidence-based reform, stakeholder collaboration, and capacity-building initiatives that align university function with national development goals and global best practice, it was concluded that the strategic management of university systems in the 21st century is critical for fostering innovative, producing globally competitive graduates and advancing socio-economic development. The insights presented aim to guide policymakers, university administrators, and education stakeholders in driving system improvements for long-term goal attainment, it was suggested among others.